Directed evolution: the quest for making enzymes useful for the industry - Salas, Paloma F. (2019)
For decades, synthetic chemists have sought to make industrial-scale catalysts as efficient and exceptionally selective as enzymes are in biological systems but, unfortunately, this task has proven evasive. Efforts then focused on making enzymes useful for the industry, and protein engineering had the task of adapting natural enzymes to work in conditions of industrial-scale processes. The approach called directed evolution is one of the models used to carry this out. Inspired by the natural evolution of species, this model proposes to evolve enzymes in an accelerated way, within the laboratory, in such a way that the manipulated enzyme exhibits the properties desired for its industrial application. Directed evolution is responsible, for example, for the industrial-scale production of enzymes included in household detergents and of the enzymes used by the pharmaceutical industry for the generation of intermediates, which are synthesized by microorganisms that express the mutated enzyme evolved in the laboratory. Today, these enzymes, some in industrial use and many others still in the exploratory stage, can catalyze very efficiently synthetic processes that form even non-natural compounds such as organosilanes  and organoboranes.